Vaccines at Work - Manuel Hoffmann; Roberto Mosquera; Adrian Chadi (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Influenza imposes substantial costs worldwide in terms of human lives and productivity losses. Vaccination could be a cost-effective way to reduce these costs for firms and public health institutions, but low take-up rates, particularly of working adults, and vaccination unintendingly causing moral hazard may decrease its benefits. We ran a natural field experiment in cooperation with a major bank in Ecuador where we modified a company-wide vaccination campaign. Experimentally manipulating incentives to participate in this health intervention allows us to study peer effects with organizational data and to determine the personal consequences of being randomly encouraged to take part in the campaign. We find that assigning employees to get vaccinated during the workweek increased take-up by 112% compared to employees assigned to the weekend, which indicates that reducing opportunity costs plays an important role to increase vaccination rates. Peer take-up also increased individual take-up significantly. Contrary to the company's expectations, we find that the effect of vaccination on health outcomes is a precise zero with no measurable health externalities from coworkers. Using a dataset of administrative records on sickness diagnoses and employee surveys, we find evidence consistent with vaccination causing moral hazard, which could decrease the effectiveness of vaccination.
Keywords: D90; I12; J01; N36; 330; Health Intervention; Flu Vaccination; Sickness-Related Absence; Field Experiment; Random Encouragement Design; Moral Hazard; Technology Adoption